Multimedia Development Of Science Learning Based On Science Literacy on The Theme of Lightning - Winda Yuningsih; Anna Permanasari; Irvan Permana (Universitas Pakuan, 2020)
This study aims to obtain: (1) multimedia design in science learning on the theme of lightning based on science literacy, (2) student science literacy information after multimedia-assisted science learning on the lightning theme, (3) student response information to multimedia in science learning based on science literacy on the lightning theme. The method used in this study was Research and Development with the ADDIE model, while the research design used pre-experimental pre-test post test only. The population in this study was grade IX students of one of the junior high schools in Cianjur district for the 2016-2017 academic year with a sample of 31 people determined using the purposive sample method. To test the feasibility of multimedia, judgments were carried out by expert lecturers, while students' science literacy data was collected by providing science literacy questions and student responses regarding multimedia were collected through questionnaires given to students. Based on the results of judgments of material experts and lecturers, it shows that aspects of multimedia design quality, aspects of multimedia attractiveness, aspects of multimedia interactiveness and aspects of material conformity with the curriculum are included in the category of excellent. From the results of data processing, it was obtained that students' science literacy abilities had a significant increase in pre-test and post-test scores. Meanwhile, students' responses to multimedia are very good in the aspect of science literacy content and aspects of potential to increase motivation, while in the aspect of ease of operating multimedia the category is good.